Manchester GATE Concert Band and Choir Performing at Roosevelt School of the Arts - Watkins, Howard::::::::: (1989)
Close-up of wind section and Ed Hull conducting orchestra With Cody Iyall wearing red sweater and Adam Watkins in 2nd row